2020
DOI: 10.3390/agronomy10071006
|View full text |Cite
|
Sign up to set email alerts
|

In-Vitro Plant Growth Promotion of Rhizobium Strains Isolated from Lentil Root Nodules under Abiotic Stresses

Abstract: Plant growth-promoting rhizobia are known to improve crop performance by multiple mechanisms. However, the interaction between host plants and Rhizobium strains is highly influenced by growing conditions, e.g., heat, cold, drought, soil salinity, nutrient scarcity, etc. The present study was undertaken to assess the use of Rhizobium as plant growth promoters under abiotic stress conditions. Fifteen Rhizobium strains isolated from lentil root nodules were tested for phosphate solubilization activity (PSA) and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 61 publications
2
6
0
Order By: Relevance
“…For instance, while characterizing rhizobia isolated from Arachis hypogaea grown under stressed environments, Khalid et al, (2020), established the P solubilization potential of eight rhizobia through the production of organic acids. Similar results have also been reported by Harsitha et al (2020), Nagalingam et al, (2020), and Sijilmassi et al, (2020) in different plants.…”
Section: The Diversity Of P Solubilizing Rhizbacteriasupporting
confidence: 91%
“…For instance, while characterizing rhizobia isolated from Arachis hypogaea grown under stressed environments, Khalid et al, (2020), established the P solubilization potential of eight rhizobia through the production of organic acids. Similar results have also been reported by Harsitha et al (2020), Nagalingam et al, (2020), and Sijilmassi et al, (2020) in different plants.…”
Section: The Diversity Of P Solubilizing Rhizbacteriasupporting
confidence: 91%
“…Catalase and oxidase enzymes reduce the oxidative damage in crop while α-amylase enzyme in the aleurone layer of seed helps in hydrolyzing the endospermic starch into sugar molecules, which provide energy for vigour index parameter. [37][38][39][40][41][42][43][44] Similar results were found by Mumtaz et al 45 who reported positive results for catalase and protease activity of Bacillus strain. He also reported the cellulose degradation ability of Bacillus strains and these enzymes were comprehensively reported for their effectiveness in tolerating stress.…”
Section: Discussionsupporting
confidence: 75%
“…These results are also supported by researcher, who described that use of phosphorous solubilization and siderophore producing bacteria enhanced shoots fresh biomass, fresh root biomass, shoot length, root length, shoot dry biomass, root dry biomass as well as total dry biomass of crop. 43 Except few bacterial strains all strains had greater efficiency of producing lytic enzymes like amylase, cellulase and chitinase. Catalase and oxidase enzymes reduce the oxidative damage in crop while α-amylase enzyme in the aleurone layer of seed helps in hydrolyzing the endospermic starch into sugar molecules, which provide energy for vigour index parameter.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table I , the levels of IAA production by isolate 194 and USDA110 tended to reduce by more than 50% under stress conditions. Sijilmassi et al (2020) ) also showed a significant reduction in IAA production by rhizobia when grown under abiotic stress conditions such as drought at ‒2 to ‒7.5 bar and concentrated salt at 0.5 to 3% NaCl. Based on this result, other PGP traits of isolate 194 and USDA110 may also be reduced under stress conditions, and this might adversely affect or could not fully facilitate plant growth under stress conditions.…”
Section: Discussionmentioning
confidence: 94%